PERAN GURU DALAM MENUMBUHKAN MOTIVASI BELAJAR PADA PESERTA DIDIK KELAS III DI SD GMIT ALIMAKE - Hia Adefia Lau (CV. ADIBA ASIHA AMIRA, 2026)
The aim of this study is to describe and analyse the role of teachers in fostering learning motivation among Year 3 pupils at GMIT Alimake Primary School, as well as to identify the factors that support and hinder this process. Learning motivation is a crucial aspect of success in primary education, particularly during the concrete operational stage in the lower years. This is a qualitative study employing a descriptive method. The data sources for this study were the headteacher and class teachers. Data collection techniques included observation, interviews and documentation. The results of the study indicate that teachers at GMIT Alimake Primary School have fulfilled their role as motivators through several strategies, including: (1) providing positive reinforcement (rewards) in the form of praise and verbal appreciation; (2) The use of varied teaching materials to stimulate pupils’ interest; (3) Creating a conducive and healthily competitive classroom atmosphere; and (4) Providing constructive feedback on pupils’ work. Nevertheless, there are challenges in the form of limited digital support facilities and variations in pupils’ socio-economic backgrounds, which affect their readiness to learn at school. The conclusion of this study confirms that the emotional bond between teachers and pupils is the key factor in maintaining stable learning motivation amongst pupils at GMIT Alimake Primary School.